2012
DOI: 10.1038/onc.2011.589
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous papillomavirus E6 oncoproteins associate with MAML1 to repress transactivation and NOTCH signaling

Abstract: Papillomavirus E6 oncoproteins associate with LXXLL motifs on target cellular proteins to alter their function. Using a proteomic approach, we found the E6 oncoproteins of cutaneous papillomaviruses Bovine Papillomavirus Type 1 (BE6) and HPV types 1 and 8 (1E6 and 8E6) associated with the MAML1 transcriptional co-activator. All three E6 proteins bind to an acidic LXXLL motif at the carboxy-terminus of MAML1 and repress transactivation by MAML1. MAML1 is best known as the co-activator and effector of NOTCH indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
133
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 74 publications
6
133
0
1
Order By: Relevance
“…Our results raise the possibility that 16E6 could recruit p53 to other non-E6AP protein complexes to which E6 is bound by LXXLL-type interactions. Cutaneous papillomavirus E6 proteins have recently been shown to interact with MAML proteins that are coactivators of Notch-induced signaling by docking on LXXLL peptides of MAML and thereby repressing MAML transcriptional activation (1,16,24); it is possible that such LXXLL peptide interactions could reshape these E6 proteins to associate with secondary targets, as was observed with 16E6 in this study. Some of the beta-group E6 proteins also associate with p300 (7); additional work will be required to determine if the p300 association with beta-group E6 is direct through p300 LXXLL interactions or if it could be analogous to the interaction of p53 with 16E6, with p300 association being triggered through prior interaction with MAML LXXLL peptides.…”
mentioning
confidence: 57%
“…Our results raise the possibility that 16E6 could recruit p53 to other non-E6AP protein complexes to which E6 is bound by LXXLL-type interactions. Cutaneous papillomavirus E6 proteins have recently been shown to interact with MAML proteins that are coactivators of Notch-induced signaling by docking on LXXLL peptides of MAML and thereby repressing MAML transcriptional activation (1,16,24); it is possible that such LXXLL peptide interactions could reshape these E6 proteins to associate with secondary targets, as was observed with 16E6 in this study. Some of the beta-group E6 proteins also associate with p300 (7); additional work will be required to determine if the p300 association with beta-group E6 is direct through p300 LXXLL interactions or if it could be analogous to the interaction of p53 with 16E6, with p300 association being triggered through prior interaction with MAML LXXLL peptides.…”
mentioning
confidence: 57%
“…Importantly, BPV-1 E6 (together with HPV-1 and -8 E6) has been recently reported to bind the mastermind-like protein 1 (MAML1), repressing the NOTCH pathway and consequent gene transcription [29]. Based on these results, the authors propose that delayed keratinocyte differentiation in papillomavirus-induced papillomas may be a consequence of impaired NOTCH signalling.…”
Section: Bpv-induced Cell Transformationmentioning
confidence: 72%
“…The E6 proteins of b-HPVs may exacerbate the mutagenic effects of UV irradiation by delaying the repair of UV-induced thymine dimers (Giampieri & Storey, 2004) through targeting of the DNA damage-response proteins ATR and XRCC1 (Iftner et al, 2002;Wallace et al, 2012) and elimination of the apoptotic response to irreparable DNA damage , which may increase genomic instability to promote tumorigenesis (Jackson et al, 2002). Expression of b-HPV E6 types HPV8 and -38 also prevents keratinocyte differentiation through targeting of MAML-1 in the Notch pathway (Brimer et al, 2012;Tan et al, 2012) and perturbs cell-survival signalling through disruption of the association of the transcriptional coactivator p300 with AKT, a key factor in promoting cell survival (Howie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…E6 proteins encoded by b-HPVs do not in general share this function; however, a recent report suggested that the HPV49 E6 protein is able to target p53 for degradation to some degree (Cornet et al, 2012), but whether this is dependent on the p53 isoform (Storey et al, 1998) et al, 2002). Expression of b-HPV E6 types HPV8 and -38 also prevents keratinocyte differentiation through targeting of MAML-1 in the Notch pathway (Brimer et al, 2012; Tan et al, 2012) and perturbs cell-survival signalling through disruption of the association of the transcriptional coactivator p300 with AKT, a key factor in promoting cell survival (Howie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation